Black Esophagus (Acute Necrotizing Esophagitis) and Wischnewsky Lesions in a Death From Diabetic Ketoacidosis: A Possible Underlying Mechanism. (June 2019) - McCarthy, Sinead; Garland, Jack; Hensby-Bennett, Sarah; Philcox, Winston; Kesha, Kilak; Stables, Simon; Tse, Rexson
Abstract : Abstract: Acute esophageal necrosis (AEN), also known as black esophagus, is a rare clinical entity. It is recently described to be associated with diabetic ketoacidosis (DKA) in a few case reports. Wischnewsky lesions (WLs) are a classic postmortem finding seen in fatal hypothermia but are recently described to be associated with DKA. Interestingly, the pathogenesis and morphology of AEN and WLs appear to share similar characteristics. Both AEN and WLs are reported to be seen simultaneously in hypothermic deaths and deaths related to alcohol abuse, but not in DKA. We report a death in a 67-year-old woman who died of DKA. At postmortem examination, the esophagus and stomach showed AEN and WLs, respectively. Although not previously reported together, both AEN and WLs have separately been described in cases of DKA. This case raises a possible unifying etiology of AEN and WLs in DKA (and probably also in hypothermic deaths and deaths related to alcohol abuse), manifested in different parts of the gastrointestinal tract.